Industry Clusters in a Middle Sized Settlement: A Case Study of Thrace Region in Turkey - Pelin Ocal; Gulden Erkut (European Regional Science Association (ERSA), 2006)
Industrial clusters are important tools for regional growth all over the world. Firms develop different kind of cooperations in different fields with their subcontractors and their competitors against competition caused by globalization and liberalization. Competition conditions force firms to be innovative at technology, design and organisation. Information flow among the firms within clusters is also necessary for innovation. Spatial concentration of firms in a specific locality is not enough but collaboration among them is also necessary in order for the firms coming together physically work as a cluster. From the theoretical point of view, industrial firms tend to move from core regions to peripherial regions. Firms which need bigger land and cheaper labour diffuse towards small towns. Size of cities is another reason of relocation of industries.In other words, firms producing more standart products decide to settle in places where they can make cheaper production. Industry located in Istanbul Metropolitan area started to move towards Thrace region after 1970's. Metropolitan city plans produced in 1970's and governments' decentralisation policies for them were the main reasons of this relocation process. In this paper, firstly, industrialization dynamics of Thrace region are described. Secondly, industry clusters and structure of industries in Corlu, which is a small industry town growing rapidly and having nearly 350 industrial firms in Thrace region, is focused upon. The results of a survey on firms were presented in this paper. The main locational determinant of firms and their main characteristics, the kind of cooperation they develop in the competition condition, main information channels between them, their innovation activities and impact on region's economy are investigated. The main research question is, whether these firms only concentrate physically or they work as a real cluster as well. From this point, it could be possible to prospect about future of the region and to find out to what extent these firms may sustain at this locality?
Keywords: 330